Evaluation of the Healthy Life Years Indicator in Conditions of EU Digitalization - Vyshnevskyi, O. (Економічний вісник Донбасу, 2019)
The paper considers the impact of digitalization on humans. An analysis of the literature showed that the problem of the impact of digitalization on the number of years of a healthy life remains insufficiently studied. As an object of study, the EU-28 member countries were selected. Since, on the one hand, the EU includes sovereign states, and on the other, it is a single labor and capital market. At the same time, the process of digitalization at the legislative level is actively supported in the EU and work is underway to build a Digital Single Market. Based on a review of literary sources and the object of study, the aim of the study is to assess the status and dynamics of “Healthy Life Years” in the context of digitalization in the EU countries. The main results. The countries leaders in digitalization not only do not show high levels in terms of the number of “Healthy Life Years”, but I can’t reduce their backlog from the countries of the leaders in terms of Healthy Life Years”. Thus, the hypothesis that “countries with a higher level of digitalization will be able to provide a greater number of “Healthy Life Years” for their citizens and its positive dynamics” has not been confirmed. No positive effect was found.